Unveiling Generation Z's Travel Motivations and Sustainable Tourism Practices: A Systematic Literature Review - Anward, Ryan; Elisabeth Simon, Helene; Tri Haryanto (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
The tourism industry is experiencing a transformative shift as the demand for sustainable practices increases, driven significantly by Generation Z. Born between the mid-1990s and early 2010s, Generation Z is characterized by their digital savviness, social awareness, and environmental consciousness. This systematic literature review (SLR) explores the travel motivations and sustainable tourism practices of Generation Z, synthesizing findings from studies published between 2018 and 2024. Our analysis reveals that Generation Z values personalized and unique travel experiences, cultural immersion, and natural attractions, heavily influenced by social media platforms and digital tools. Despite their strong preference for eco-friendly travel options, there is a notable gap between their environmental attitudes and actual sustainable behaviors. Cross-cultural differences also significantly shape sustainable tourism preferences within Generation Z. This study underscores the need for targeted educational and marketing strategies to bridge this gap and highlights the importance of integrating advanced digital technologies in tourism strategies. The findings provide valuable insights for tourism stakeholders to develop tailored marketing campaigns, sustainable tourism products, and policies that align with Generation Z's values, contributing to the broader academic discourse on sustainable tourism.